HUBUNGAN USIA KEHAMILAN DENGAN BERAT BADAN BAYI LAHIR DI KLINIK PRATAMA ATHALLAH TAHUN 2024 - Kirana, Alifia Nova; Elsya Hildatriana; Husnul Mazidah; Lusi Triwahyuni; Pujiati; Ambariani (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2025)
During pregnancy, birth weight is a crucial metric for evaluating the fetus's development and health. The risk of newborn morbidity and death as well as future growth and development issues are predicted by this characteristic. At the Athallah Primary Clinic, the aim of this research was to ascertain the correlation between child birth weight and gestational age. With a cross-sectional methodology, this research is quantitative in nature. 134 respondents who gave birth at the Athallah Primary Clinic in 2024 were sampled in total using this method. The study's dependent variable was the weight of the newborn, whereas the independent variable was gestational age. Using the chi-square test, data were examined both univariately and bivariately. This research found that the newborn birth weight at the Athallah Primary Clinic in 2024 was significantly correlated with the mother's gestational age (p-value 0.008).